Flexor and extensor muscle tone evaluated using the quantitative pendulum test in stroke and parkinsonian patients. (May 2016) - Huang, Han-Wei; Ju, Ming-Shaung; Lin, Chou-Ching K.
Highlights: Pendulum test cannot differentiate hypertonia of stroke and PD. Muscle tone are higher in elbow extensor for both stroke and PD patients. Hypertonia of both parkinsonian and stroke patients is velocity dependent. Abstract: The aim of this study was to evaluate the flexor and extensor muscle tone of the upper limbs in patients with spasticity or rigidity and to investigate the difference in hypertonia between spasticity and rigidity. The two experimental groups consisted of stroke patients and parkinsonian patients. The control group consisted of age and sex-matched normal subjects. Quantitative upper limb pendulum tests starting from both flexed and extended joint positions were conducted. System identification with a simple linear model was performed and model parameters were derived. The differences between the three groups and two starting positions were investigated by these model parameters and tested by two-way analysis of variance. In total, 57 subjects were recruited, including 22 controls, 14 stroke patients and 21 parkinsonian patients. While stiffness coefficient showed no difference among groups, the number of swings, relaxation index and damping coefficient showed changes suggesting significant hypertonia in the two patient groups. There was no difference between these two patient groups. The test starting from the extended position constantly manifested higher muscle tone in all three groups. In conclusion, the hypertonia of parkinsonian and stroke patients could not be differentiated by the modified pendulum test; the elbow extensors showed a higher muscle tone in both control and patient groups; and hypertonia of both parkinsonian and stroke patients is velocity dependent.